Smart Control Upgrade: IoT-Enhanced Remote Management of Straightening Machine with NodeMCU ESP8266 - Irawan, Bambang; Muhlasin, Muhlasin; Erzed, Nixon; Herwanto, Agus; Rahaman, Mosiur; Mooduto, Hanriyawan Adnan (JOIV : International Journal on Informatics Visualization, 2025)
Straightening machines are essential in the oil and gas industry. These machines are intended to straighten bent drill pipes after the drilling process. The operator must be near the straightening machine for manual operation and control. This limitation prevents the operator from monitoring the machine's performance directly and efficiently. In response to this challenge, this study proposes to use the Internet of Things to enable remote control and monitoring of the straightening machine using the NodeMCU ESP8266 microcontroller. The proposed system integrates sensors and electronic components to collect and process critical data from the straightening machine. The INTER-METH method develops an IoT system to control the straightening machine remotely. The RemoteXY cloud server receives the collected data via a Wi-Fi network using the Message Queuing Telemetry Transport protocol. This setup enables real-time data retrieval by an Android-based application. The proposed system allows the user to monitor the machine's operational status and control it remotely, thereby increasing efficiency by up to 45% and reducing the total cost of operation by about 60%. With the implementation of IoT, the operator could remotely monitor the performance of the straightening machine, thereby increasing operator safety by more than 50%. These advances improve operators' safety conditions and simplify maintenance and operational processes. In addition, future research could focus on robust data security measures. These developing systems could be operated with other industrial IoT platforms and utilize data analytics for predictive maintenance, extending the machine's life.